MoS2–Plasmonic Hybrid Platforms: Next-Generation Tools for Biological Applications - Nayra A. M. Moussa; Seungah Lee; Seong Ho Kang (Nanomaterials)
The combination of molybdenum disulfide (MoS2) with plasmonic nanomaterials has opened up new possibilities in biological applications by combining MoS2’s biocompatibility and high surface area with the optical sensitivity of plasmonic metals. These MoS2–plasmonic hybrid systems hold great promise in areas such as biosensing, bioimaging, and phototherapy, where their complementary properties facilitate improved detection, real-time visualization, and targeted therapeutic interventions. MoS2’s adjustable optical features, combined with the plasmon resonance of noble metals such as gold and silver, enhance signal amplification, enabling detailed imaging and selective photothermal or photodynamic therapies while minimizing effects on healthy tissue. This review explores various synthesis strategies for MoS2–plasmonic hybrids, including seed-mediated growth, in situ deposition, and heterojunction formation, which enable tailored configurations optimized for specific biological applications. The primary focus areas include highly sensitive biosensors for detecting cancer and infectious disease biomarkers, high-resolution imaging of cellular dynamics, and the development of phototherapy methods that allow for accurate tumor ablation through light-induced thermal and reactive oxygen species generation. Despite the promising advancements of MoS2–plasmonic hybrids, translating these platforms into clinical practice requires overcoming considerable challenges, such as synthesis reproducibility, toxicity, stability in physiological conditions, targeted delivery, and scalable manufacturing. Addressing these challenges is essential for realizing their potential as next-generation tools in diagnostics and targeted therapies.